Analisis Hambatan Belajar Secara Metode Zoom Pada Mahasiswa Keperawatan Selama Masa Pandemi Covid 19 di Universitas Malahayati Bandar Lampung Tahun 2019 – 2023 - Epilasari Epilasari; Rilyani Rilyani; Aryanti Wardiyah; Anita Bustami (Malahayati Nursing Journal, 2024)
ABSTRACT Learning problems during the pandemic experienced changes and problems where students were required to study at home using zoom media. Data on the number of nursing students for the 2019-2021 period at Malahayati University, a total of 154 people. About 56% of students experience problems with lack of knowledge and mastery of material in zoom activities, while 44% are due to factors from the internet network in the learning room which is difficult to access. The purpose of this research is to find out the learning barriers using the zoom method for nursing students during the Covid 19 pandemic at the Malahayati University in Bandar Lampung in 2023. The research will be carried out in February 2023 at the Nursing Study Program, Faculty of Health, Malahayati University, Bandar Lampung. This type of observational analytic research with a quantitative research design and cross sectional approach. The research was conducted using primary data from a questionnaire. The frequency distribution of online learning barriers based on internal factors was very high category 49 (44.1%), high barriers 21(18.9%) moderate barriers 14 (12.6%), very low barriers 16 (14.4%), very low barriers 11 (9.9%). Frequency distribution of online learning barriers based on external factors with very high category 49 (36.9%), high barriers 17(15.3%) moderate barriers 21 (18.7%) respondents, very low barriers 19 (17.1%) ), very low resistance 13 (11.7%). The conclusion is that there are learning barriers using the zoom method for nursing students during the Covid 19 pandemic at the University of Malahayati Bandar Lampung in 2023. It is expected to be able to increase understanding of learning techniques using zoom media. Keywords: Online Barriers, Covid 19, Internal and External Barriers  ABSTRAK Masalah pembelajaran pada masa pandemi mengalami perubahan dan masalah dimana mahasiswa diharuskan untuk belajar di rumah dengan menggunakan media zoom. Data jumlah mahasiswa/i perawat periode 2019-2021 di Universitas Malahayati, sejumlah     154 orang.Dari sekitar 56% mahasiswa mengalami masalah kurangan pengetahuan dan menguasai materi dalam kegiatan zoom, sedangkan 44% dikarenakn faktor dari jaringan internet di ruangan pemberlajaran susah untuk di akses. Tujuan untuk mengetahui hambatan belajar secara metode zoom pada mahasiswa keperawatan selama masa pandemi Covid 19 Di Universitas Malahayati Bandar Lampung Tahun 2023. Penelitian dilaksanakan pada bulan Februari 2023 di Program Studi Keperawatan Fakultas Kesehatan Universitas Malahayati Bandar Lampung. Jenis penelitian analitik observasional dengan desain penelitian kuantitatif dan pendekatan cross sectional. Penelitian dilakukan dengan menggunakan data primer dari kuesioner. Distribusi frekuensi hambatan belajar secara daring berdasarkan faktor internal kategori sangat tinggi 49 (44,1%), hambatan tinggi 21(18,9%) hambatan sedang 14 (12,6%), hambatan rendah 16 (14,4%), hambatan sangat rendah 11 (9,9%). Distribusi frekuensi hambatan belajar secara daring berdasarkan faktor eksternal dengan kategori sangat tinggi 41 (36,9%), hambatan tinggi 17(15,3%) hambatan sedang 21 (18,7%) responden, hambatan sangat rendah 19 (17,1%), hambatan sangat rendah 13 (11,7%). Ada hambatan belajar secara metode zoom pada mahasiswa keperawatan selama masa pandemi Covid 19 Di Universitas Malahayati Bandar Lampung Tahun 2023. Diharapkan mampu meningkatkan pemahaman mengenai teknik pembelajaran menggunakan media zoom Kata Kunci: Hambatan Metode Zoom, Covid 19, Hambatan Internal Dan Eksternal